Brand Image and Brand Love as Mediation of Brand Experience on Brand Loyalty in Samsung Smartphone Customers - Prasidha, Helmi Afif; Rohman, Fatchur; Sunaryo, Sunaryo (Universitas Brawijaya, Indonesia, 2024)
This study aims to determine the variables affecting consumer loyalty to a smartphone brand. For this reason, researchers use Samsung smartphones in Malang City as research objects. 160 responses were obtained using a nonprobability approach with a purposive sampling technique. The data was collected through a questionnaire, then analyzed using the Partial Least Square analysis tool and measured using a Likert scale. The results of this study found that brand experience has a significant effect on brand loyalty. Also, brand image and love are proven to mediate the impact of brand experience on brand loyalty partially. It is necessary to re-explore other independent variables related to cognitive aspects that directly affect loyalty to the same research object or other smartphone brands, such as brand ambassadors, self-congruity, celebrity endorsement, and other factors available.